Experiences of people with long COVID: Symptoms, support strategies and the Long COVID Optimal Health Programme (LC‐OHP) - Hiyam Al‐Jabr; David R. Thompson; David J. Castle; Chantal F. Ski (Health Expectations)
Abstract Introduction Long COVID (LC) is a multisystem illness, with fluctuating symptoms that affect the daily activities of patients. There are still no standardised diagnostic criteria or treatment approaches for managing LC. The LC‐Optimal Health Programme (LC‐OHP) was designed to support the mental wellbeing and physical health of people with LC. Gaining an in‐depth understanding of patients' experiences and support strategies is imperative to identifying appropriate supports to guide them through their recovery. This study aimed to elicit the experiences and perceptions of adults with LC regarding symptoms, support strategies and the LC‐OHP. Methods As part of a wider randomised controlled trial of the LC‐OHP, participants in the intervention group had their sessions audio‐recorded. Transcripts were thematically analysed to identify common emergent themes. Findings The LC‐OHP was delivered to 26 participants. Data were collected between January 2022 and February 2023. Four main themes emerged: ‘Symptoms and impact of LC’; ‘Other sources of support and perceived challenges’; ‘Strategies to support LC’ and ‘Perceptions of the LC‐OHP’. Conclusion LC experiences were mostly described as fluctuating and burdensome that significantly impacted daily activities, and physical and mental health. The LC‐OHP was perceived as beneficial. Access and experiences of other sources of support were varied. Increasing LC awareness amongst health practitioners and the wider community has the potential to improve the experiences of those affected by LC. Patient or Public Contribution The LC‐OHP was derived from the OHP. It was adapted to people with LC following consultation with practitioners at an LC clinic. Additionally, the mode and timing of delivering the programme to this population were taken into account for its delivery at the convenience of participating patients. While considering that fatigue and brain fog are amongst the most reported complaints of people with LC, public members with LC were not involved directly in this study; however, feedback obtained from practitioners working with this population was implemented in amending the programme and its delivery. Additionally, feedback from patients with other chronic health conditions who used the OHP in previous studies has been implemented to make the programme more user‐friendly. Moreover, feedback obtained from participants receiving this programme in this study was implanted immediately and shared with other participants. Finally, this study was overviewed by a data management committee that included two public members with LC, who contributed and provided guidance to support this study.